(untitled) (Journal of Economic Research & Business Administration, 2021)
In this era of extraordinary change and globalization, many recognize that the creative industries are driving the new economy. Industries of the creative sector of the economy are increasingly recognized as significant for both social and economic development and are attracting growing interest of the world community. The understanding and study of the economic value of creative industries has expanded. It was clear that they have an impact on GDP growth and employment and can improve the foreign trade position and competitiveness of the country, as well as contribute to revitalizing and promoting the brand of creative cities and attracting investment. Many authors recognize that creative industries have a significant impact on the development of the economy and society, thanks to the implementation of a new concept of economic growth and development, and that they represent one of the few economic sectors in which dynamic development is expected in the future. This review presents the research results of a study of the development of creative industries in one of the Post-Soviet countries – Kazakhstan. The research methodology, including the analysis of interviews, reveals several barriers to the development of the creative sector of the economy. This study helps us understand how the creative economy is developing in a transition country. Key words: creative industries, creative economy, barriers, Kazakhstan.